There’s no answer choices to answer
Answer:
(2, 7 )
Step-by-step explanation:
Given the 2 equations
y = 2x + 3 → (1)
y = 3x + 1 → (2)
Substitute y = 3x + 1 into (1)
3x + 1 = 2x + 3 ( subtract 2x from both sides )
x + 1 = 3 ( subtract 1 from both sides )
x = 2
Substitute x = 2 into either of the 2 equations for corresponding value of y
Substituting x = 2 into (1)
y = 2(2) + 3 = 4 + 3 = 7
Solution is (2, 7 )
X+.75=12.25
X+.75-.75=12.25-.75
X=11.50
11.50 wasMarietta's wage before her raise
The two numbers are 16 and 42.
Answer:
length times width
Step-by-step explanation: